Instructional Counselling for Cognitive Competence - Martin, Jack (Canadian Journal of Counselling and Psychotherapy, 2011)
Competence is the ability to engage the thoughts, actions, and motivation necessary to accomplish goals. Cognitive competence refers to the internal structure of information and internal processes for transforming this information that underlie displays of competence. Contemporary ideas from cognitive science are employed to develop a general model of cognitive competence. Counselling is defined as a prescriptive, instructional activity concerned with assisting clients to acquire levels of cognitive competence that will allow them to achieve their goals. The instructional counselling approach developed by Martin and Hiebert (1982, in press) is used to demonstrate how counselling can impact various elements comprising the cognitive competence of clients in relation to their concerns and problems.